Comparative Study of Electric Machines for Stirling Generator Application. - CHETANGNY, Patrice Koffi; ZOGBOCHI, Victor; Aredjodoun, Jacques G.; CHAMAGNE, Didier; BARBIER, Gérald; HOUNDEDAKO, SOSSOU; VIANOU, Antoine (My University, 2021)
The choice of a machine for an application and a given specification remains a complex problem. This will involve, for example, bringing together criteria such as: performance, space saving, economical, reliable, little acoustic noise and others. The best machine selection to fulfill all constraints is an important step for the project to be realized. This work focus on Stirling Engine based Generator and study all types of rotating machines that can be employed for maximum electric power production. Analytical electromagnetic models where developed for all types of rotating machines that satisfied minimum requirement for the project by solving Maxwell equations. The purpose is to develop the design model and combine electromagnetic and thermal study of the machines. Finite Element Method is used to compare the performances of the generators for the best choice. Results show that for applications not requiring bigger output power, the major criteria for the selection is the optimal magnetic induction created by the inducer in the stationary part of the machine. For application such as Stirling generators, permanent magnet (PM) machine satisfy many comparison criteria such as maximum power at low speed, torque density, high efficiency. Beyond exposing a selection method for a project, this work lay down a step-by-step method for engineers and scientists for the crucial stage of design and conception work
Keywords: Analytical Model; Choice of Machines; Efficiency; FEM; Maximum Power